Prenatal care in a primary healthcare center for imprisoned pregnant women - Maria do Carmo Silva Fochi; Agnês Raquel Camisão da Silva; Maria Helena Baena de Moraes Lopes (Universidade Federal do Ceará, 2014)
This experience report aimed to describe the prenatal care undertaken in a primary care center in the non-metropolitan area of the State of São Paulo, offered to the female prison population. The data and related information refer to the period June 2010 - June 2012. The article describes the construction of the work process by the local team, the dynamics of providing the attendance, the human resources involved and the consultations undertaken. The prenatal care provided to the pregnant women made it possible to investigate the pluralized universe of imprisoned women and their needs resulting from the condition of being pregnant in the prison environment. Thus, decent attendance to the prison population's health - a human and constitutional right - is considered important, so as to avoid physical, emotional and social problems, which in the pregnant woman may be passed on to her child.